Analisis Rancangan Model Interaksi Manusia dan Komputer Modern pada Sistem Evaluasi Kegunaan Berbasis Kecerdasan Buatan Menggunakan Metode Design Science Research dan Algoritma Pembelajaran Mesin - Sofyan Nur Salim; Ire Puspa Wardhani (TIN: Terapan Informatika Nusantara, 2026)
The usability evaluation system at STMIK Jakarta STI&K is a digital learning platform, campus website, academic information system, or other supporting applications used in an efficient and satisfying campus environment for the academic community. Users here include students, lecturers, administrative staff, and parents. This usability evaluation helps identify problems that may hinder the lecture process or administration system, so that they can be fixed for a better experience. STMIK Jakarta STI&K currently relies heavily on the digital platform ecosystem, but crucial usability evaluations are still constrained by traditional management methods that are inefficient, subjective, and difficult to scale. This thesis research aims to overcome these limitations by designing a modern Human-Computer Interaction (HCI) model integrated with Artificial Intelligence (AI) Technology. Using the Design Science Research (DSR) paradigm, this thesis research validates the problems that exist at STMIK Jakarta STI&K through a preliminary survey and continues to the design stage of a conceptually evaluated model. The main result of this study is a conceptual model of a holistic usability evaluation system. The model to be built is a model in the form of computer architecture, functionality, algorithms, or interfaces. which integrates Machine Learning, Computer Vision, and Natural Language Processing capabilities for data analysis, by adopting the human-in-the-loop principle. The final results of this research will later provide new innovations for STMIK Jakarta STI&K which are smarter and more efficient, and contribute as a blueprint for development and theoretical foundation in the field of AI-based HCI.